Comparative Study of Product Development Processes in SME Merchandise Through the Double Diamond Process Model - Mardiana, Shafa Chairunida; Riyadhi, Slamet; Ariseno, Nisrina Mozza Khairunnisa (Avenew Indonesia, 2025)
This research focuses on a comparison of the product development process in the SME merchandise industry in the city of Bandung, especially in the apparel sector, which shows great potential for innovation. The lack of the designer's role in some SMEs has led to a lack of product innovation and uniqueness. This study aims to analyze the differences between design-oriented and production-oriented approaches in the development of merchandise products with the aim of increasing the efficiency, added value, and competitiveness of MSMEs in the market through the application of the Double Diamond process model. By using a qualitative approach through observation and in-depth interviews, this study chose McBlush Gift and Sugar Souvenir as the objects of study to compare the implementation of the Double Diamond model in the development of merchandise products. The research findings reveal significant differences in objectives, key stakeholders, and key activities at each stage of the Double Diamond model between McBlush Gift, which focuses on new product innovation, and Sugar Souvenir, which tends to take an iterative approach to improving existing products. This research provides valuable insights into the role of the designer and the integration of the Double Diamond model in increasing the effectiveness of MSME merchandising product development in a competitive market.